2010
DOI: 10.1007/s11633-010-0123-6
|View full text |Cite
|
Sign up to set email alerts
|

A bit-level text compression scheme based on the ACW algorithm

Abstract: This paper presents a description and performance evaluation of a new bit-level, lossless, adaptive, and asymmetric data compression scheme that is based on the adaptive character wordlength (ACW(n)) algorithm. The proposed scheme enhances the compression ratio of the ACW(n) algorithm by dividing the binary sequence into a number of subsequences (s), each of them satisfying the condition that the number of decimal values (d) of the n-bit length characters is equal to or less than 256. Therefore, the new scheme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…This section presents a description of the data compression scheme that shall be used in this search engine model, namely, the adaptive character wordlength (ACW(n,s)) scheme [14]. This scheme is based on the adaptive character wordlength (ACW(n)) algorithm [15], therefore, it will be described first.…”
Section: The Data Compression Schemementioning
confidence: 99%
See 1 more Smart Citation
“…This section presents a description of the data compression scheme that shall be used in this search engine model, namely, the adaptive character wordlength (ACW(n,s)) scheme [14]. This scheme is based on the adaptive character wordlength (ACW(n)) algorithm [15], therefore, it will be described first.…”
Section: The Data Compression Schemementioning
confidence: 99%
“…A data compression scheme that satisfies this requirement is the recently developed adaptive character wordlength (ACW(n,s)) scheme [14,15], therefore, it will be used in this work. Recent investigations on using this scheme for text compression demonstrated an excellent performance in comparison with many widely-used data compression algorithms and state-of-the-art tools [14,15]. This paper is organized in 7 sections.…”
Section: Introductionmentioning
confidence: 99%
“…However, the decoding speed of this technique is relatively slow. Bahadili and Hussain (2010) presented a new bit level adaptive data compression technique based on ACW algorithm, which is shown to perform better than many widely used compression algorithms in terms of compression ratio. Hermassi et al (2010) showed how a symbol can be coded by more than one codeword having the same length.…”
Section: Banetley Et Al (1986) Introduced a New Compression Techniqumentioning
confidence: 99%
“…Actually the importance of lossless data compression is it doesn't allow any data loss. Even if a single bit of data is lost after decoding, that determines the file is corrupted [3] [4].The most attractive part of data compression is compressing data in a database system. The performance is immensely improved because smaller size of physical data are needed to be moved for any operation on the database [1] [2].…”
Section: Introductionmentioning
confidence: 99%